Biological monitoring : an introduction - Hee, Shane Que. ([S.l.] : Wiley, 1993)
This definitive source provides practicing professionals and students in the occupational, environmental, and public health and safety fields with the functional basics of biological monitoring. The author examines how environmental exposures to particular chemicals are related to concentrations of markers in body tissues and fluids. Biological Monitoring integrates the applied sciences of industrial/environmental hygiene, epidemiology, public health, occupational medicine, toxicology, biochemistry, and analytical chemistry with the basic sciences to interpret the connections between exposures and lifestyle/environmental influences, and their effects on humans. This comprehensive introduction provides dependable, detailed coverage of: * monitoring for harmful substances in the workplace * the benefits and limitations of testing for critical levels of toxic materials in bodily tissues and fluids * state-of-the-art developments in biological monitoring * a wide variety of toxic chemicals and selected physical agents * immunoassays * monitoring for HIV and AIDS * importance of exposure routes * the most up-to-date methods of health and medical surveillance * the interpretation of adduct concentrations * biological exposure indices * biological monitoring of pesticides * biological monitoring in the home and around hazardous waste sites * and much more This essential, compelling guide is the only inclusive and thorough introduction available. Biological Monitoring's rigorous, accessible, interdisciplinary approach makes this an invaluable reference and text for industrial and environmental hygienists, physicians, pharmacists, nurses, epidemiologists, toxicologists, laboratory technicians, chemical engineers, science graduate students, and the environmentally concerned.
Keywords: biology